The Workshop on Waste Treatment of Rambutan Peel and Rambutan Seeds by KKN Kebangsaan UNS in Mawar Mekar Village, Kapuas, Central Kalimantan: Workshop Pengolahan Limbah Kulit Rambutan dan Biji Rambutan Oleh KKN Kebangsaan UNS di Desa Mawar Mekar, Kapuas, Kalimantan Tengah - Zuhri, Moh Sayful; Sudibya; Eksa Rusdiyana; Erikson Vri Anugrah Aritonang; Elisa Tri Rahmawati; Hadhika Afghani Imansyah; Kania Quinny Carristia; Nadiya Fistianati Aunillah (PELITA NUSA TENGGARA, 2022)
Mawar Mekar Village is one of the villages located in Pulau Petak District, Kapuas Regency where agriculture is the main sector of the village economy. The main agricultural products of this village are rice, rambutan, chili, and other commodities. With a land area of ​​20 hectares, rambutan commodity can potentially increase the economy of rural communities. However, the knowledge of the villagers is limited to the use of rambutan fruit, only the flesh of the fruit, thus causing waste in the form of seeds and skin. Therefore, there is a need for reprocessing measures to reduce the waste. Community service activities are carried out through a Real Work Lecture (KKN) approach by Sebelas Maret University students who are members of the National Community Service Program. Departing from these problems, KKN students innovate to make products from rambutan skin and seeds that have high economic value. The community service program is packaged through real work lecture activities and is expected to provide benefits in the program. Through this program, he hopes to be able to provide the role of academics in devoting themselves to the community, as well as opening up opportunities for Village MSMEs that will help the village economy.